2020
DOI: 10.1016/j.psj.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

An EAV-HP insertion in the 5ʹ flanking region of SLCO1B3 is associated with its tissue-expression profile in blue-eggshell Yimeng chickens (Gallus gallus)

Abstract: We previously reported that blue eggshell color in chickens is associated with a partial endogenous retroviral ( EAV-HP ) insertion in the promoter region of the solute carrier organic anion transporter family member 1B3 ( SLCO1B3 ) gene. The EAV-HP sequence includes numerous regulatory elements, which may modulate the expression of adjacent genes. To determine whether this insertion influences the expression of neighboring genes, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The difference in the expression of SLCO1B3 between IM+ and IM− chickens was also validated by the qPCR analysis (Fig. S1 ), the primers for which have been described in a previous study 25 . The expression levels of the SLCO1B3 and OATP1B3 in IM+ chickens were both approximately 1/twofold compared with those in IM− chickens.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…The difference in the expression of SLCO1B3 between IM+ and IM− chickens was also validated by the qPCR analysis (Fig. S1 ), the primers for which have been described in a previous study 25 . The expression levels of the SLCO1B3 and OATP1B3 in IM+ chickens were both approximately 1/twofold compared with those in IM− chickens.…”
Section: Resultssupporting
confidence: 58%
“…In humans, SLCO1B3 is mainly expressed in the liver and its encoded protein OATP1B3, plays an important role in endogenous and exogenous transport processes, which has a closely relationship with bile acids and drug metabolism in liver 3 , 20 . Our previous research also showed that chicken SLCO1B3 was mainly expressed in liver, and the SLCO1B3 homolog gene SLCO1B1 had exceptionally low expression levels in the liver 25 . This may indicate that in chickens, SLCO1B3 plays more important role in the endogenous and exogenous transport processes in the liver.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations